Family Violence (Kriminalističke teme, 2004)
Everyday violence, manifested in the street, at work, in the public media, all types of interpersonal communication, slowly but surely, is being transferred to a family. Family violence, wich is more and more increasing, is a reflection of global crises of valuse of the society, threatening to destroy family as a foundation of social community. Destruction of family as an institution brings into question the existence of society or state itself.In this Article, the author will present her standpoint on viloance and its cosequences in Bosnia and Herzegovina. The. idtimate goal of the author is to point at measures thet shoidd be taken in order to protect persons that are victims of this violence.